Penerapan Kebijakan Aplikasi Tourism Makassar Sebagai Media Promosi Di Dinas Pariwisata Kota Makassar - Hijriah, Usman Umratul; Mappamiring, Mappamiring; Amiruddin, Iswadi (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2025)
The aim of the research is to determine the implementation of the Makassar Tourism Application Policy as a Promotional Media in the Makassar City Tourism Office. This type of research is qualitative research with descriptive research type. Data collection techniques use observation, interviews and documentation methods. The results of the research are that communication in the Makassar Tourism application at the Makassar City Tourism Office always prioritizes communication, the communication referred to here is socialization. Therefore, each field always holds activity meetings in each field so that employees can communicate directly with tourists who come from outside Sulawesi so they can implement a good and polite communication system towards tourists. Resources in the existing Makassar Tourism application. The Makassar City Tourism Office continues to strive to improve the human resources in the office, because Makassar City is a city that is famous for its tourist attractions that can attract tourists, culinary food, etc.